Prolonged time to treatment of biologics in inflammatory bowel disease: disparities from a retrospective study in a tertiary referral centre in the UK - Charlotte Wong; Paul Bassett; Nikolaos Kamperidis; Ravi Misra; Lisa Younge; Lovesh Dyall; Katie Yeung; Christy Rejee; Naila Arebi (BMC Gastroenterology)
Abstract Background Several disparities in healthcare utilisation and delivery are reported in inflammatory bowel disease (IBD). We examined disparities for delays in biologic administration. Methods This is a tertiary centre, retrospective, cohort study of consecutive adult IBD outpatients referred to the biologics clinic (BC) for initiation of therapy over 2 years. We collected patient-, disease- and service-related data in addition to adverse clinical outcomes (primary non-response, corticosteroid prescription, IBD hospital admission and surgery) within 6 months of the first dose of therapy. The primary outcome was time-to-therapy (TTT): time interval from referral to the first drug dose. Univariate and multivariate regression analyses examined associations between variables and TTT. Results 240 patients started biologics: 87 (36%) ulcerative colitis (UC) and 153 (64%) Crohn’s disease (CD). Median referral age was 43 years (IQR 34–56) and 128 (53%) were male. Charlson Comorbidity Index was ≤ 1 in 185 patients (77%) and 141 (59%) were biologic naïve. 91 (37.9%) were White British, 88 (36.7%) Asian (Indian or Pakistani), 61 (25.4%) were from other ethnic groups. Median TTT was 76 (IQR 56–97) days. In multivariable analysis, longer TTT was associated with CD, other ethnic groups and Adalimumab. Lack of funding at the time of BC and referral age were of borderline statistical significance. Adverse outcomes at 6 months was significantly associated with C-reactive protein level > 10 mg/L (OR 2.13; p = 0.03) but not with longer TTT. Conclusions Delays in initiating biologic therapy are significantly associated with IBD type, ethnicity and therapy type. Unwarranted variation in IBD care can be mitigated by concerted initiatives to address modifiable factors for timely access to effective therapies.